By birth or consent : children, law, and the Anglo-American revolution in authority - Brewer, Holly, 1964-; Omohundro Institute of Early American History & Culture (Chapel Hill ; London : Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, by the University of North Carolina Press, 2005)
"In By Birth or Consent, Holly Brewer explores how the changing legal status of children illuminates the struggle over consent and status in England and America. The concept of meaningful consent, as it emerged through religious, political, and legal debates, challenged the older order of birthright and became central to the development of democratic political theory." "As Brewer demonstrates, the legal status of children serves as a clear measure of the changing foundations of political and legal authority from the sixteenth through the eighteenth centuries. Age was central to this shift to a consent-based ideology, which specifically excluded children from the practice of consent." "Brewer's analysis reshapes the debate about the origins of modern political ideology and makes connections between Reformation religious debates, Enlightenment philosophy, and democratic political theory."--Jacket
Introduction : Limiting and developing individual consent : children and Anglo-American revolutionary ideology -- ch. 1. Children, inherited power, and patriarchal ideology -- ch. 2. "Borne that princes subjects"? or "Christianity is no man's birth right"? : the religious debate over inherited right and consent to membership -- ch. 3. The dilemmas of government by consent and the problem of children : force, influence, implied consent, and inherited obligation -- ch. 4. Subjects of citizens? : inherited right versus reason, merit, and virtue -- ch. 5. "To stop the mouths" of children : reason and the common law -- ch. 6. Understanding intent : children and the reform of guilt and punishment -- ch. 7. The emergence of parental custody : children and consent to contracts for land, goods, and labor -- ch. 8. "Partly by persuasions and partly by threats" : parents, children, and consent to marriage -- The empire of the fathers : from birth to consent of whom? -- Appendix : Legal treatises used by Americans before the nineteenth century -- Index.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record; online resource viewed March 3, 2017.
eBooks on EBSCOhost
Keywords: Minors -- England -- History; Children -- Legal status, laws, etc. -- England -- History; Capacity and disability -- England -- History; Children -- England -- Social conditions; Children -- Legal status, laws, etc. -- United States -- History; Capacity and disability -- United States -- History; Social contract -- History; Mineurs (Droit) -- Angleterre -- Histoire; Enfants -- Droit -- Angleterre -- Histoire; Incapacité (Droit) -- Angleterre -- Histoire; Enfants -- Angleterre -- Conditions sociales; Enfants -- Droit -- États-Unis -- Histoire; Incapacité (Droit) -- États-Unis -- Histoire; Contrat social -- Histoire; HISTORY -- United States -- Colonial Period (1600-1775); LAW -- Administrative Law & Regulatory Practice; Capacity and disability; Children -- Legal status, laws, etc; Children -- Social conditions; Minors; Social contract; England; United States; Minderjarigen; Rechtspositie; Beslissingsbevoegdheden; Klassentegenstellingen; History